University Transformations and the New Knowledge Production Regime in Informational Capitalism - Maxime Ouellet; Éric Martin (tripleC: Communication, Capitalism & Critique, 2018)
This article examines undergoing transformations in universities in the context of the structural crisis of capitalism, which began more than 40 years ago. This crisis is at the heart of one of the main contradictions of capitalism: while capital needs living labour to produce value, the dynamic of accumulation requires the replacement of human labour by machines. We will show how capital attempts to overcome this contradiction by modifying the nature of knowledge, learning institutions and human beings to turn them into productive investments, whose profitability can be measured. The contemporary mutations of universities are linked to the globalization, financialization and commodification of knowledge. We also observe transformations in universities’ institutional arrangements and in individual human consciousness. Our perspective combines institutionalist political economy and Marxian critique of value, showing how material, institutional and cultural transformations are dialectically articulated in a new form of social regulation. We will show how there is a complementarity between the transformations of political, economic and learning institutions and their linkage with a new mode of knowledge production. The general goal being that advanced mastery of knowledge and information will increase the efficiency of the technological and economic system and its endless acceleration.